Assessment of the effect of living wall systems on the improvement of the urban heat island phenomenon. (15th August 2020) - Shafiee, Elham; Faizi, Mohsen; Yazdanfar, Seyed-Abbas; Khanmohammadi, Mohammad-Ali
Abstract: The main objective of this research is to study the effect of a panel living wall on the ambient air temperature and its effect on reducing day and night temperature fluctuations. A living wall has been introduced as an appropriate way to reduce the urban heat island phenomenon. To achieve the purpose, a living wall was applied to the body of a controllable chamber, and two data loggers for temperature and humidity were used. In the first experiment, three types of walls, including a wall without plants, a wall with panels and a living wall, are compared for three consecutive days. In the second experiment, a device is placed adjacent to the living wall and another is placed in the same condition in front of a part of the wall that does not have plants. These data were recorded for 24 h a day over 10 days and compared. This research was conducted in Shiraz, Iran, which has a hot, semi-arid climate. To validate the results, a computer simulation with the ENVI-met program was used. The results show that the panel living wall system can reduce the ambient air temperature by up to 8.7 °C. Additionally, the living wall reduces the temperature fluctuations by decreasing the maximum and increasing the minimum temperatures of the ambient air. During the hours of solar radiation, the temperature dropped by an average of 2.59 °C. It is concluded that living walls can effectively improve the urban heat island phenomenon by reducing its surroundings' temperatures. Highlights: A living wall has been introduced as an appropriate way to reduce the urban heat island phenomenon. A living wall reduces the temperature fluctuations by decrease the maximum and increases the minimum temperatures. To validate results, a computer simulation with the Envi-met program has been used. Living walls prevent the temperature from rising by increasing the humidity of the environment on hot days. The living walls can effectively improve the urban heat island phenomenon by reducing its surroundings temperatures.